Pengaruh Jenis Kemasan pada Perubahan Kualitas Salak Pondoh Banjarnegara dalam Bentuk Tandan Selama Transportasi dan Penyimpanan - Rafika Ratik Srimurni; Indah Yuliasih; Emmy Darmawati; Yenny Muliani; Mega Herdiana (Jurnal Ilmu Pertanian Indonesia, 2024)
Salak (Salacca edulis Reinw.) in bunch form can be attractive to consumers because its own unique shape. The use of primary and secondary packaging can maintain fruit quality. This study aims to evaluate quality change of salak in bunches including physical damage, mechanical damage, physiological and microbiological damage. Salak bunches were stored for 22 days, with observations every 3 days to analyze fruit damage, TSS, weight loss, and fruit hardness. The study used a single-factor completely randomized design, involving 3 treatments: wooden crates (K1), cardboard without net foam (K2), and cardboard with net foam (K3). Data were analyzed descriptively, analysis of variance, and DMRT at the 5% level. Primary packaging was effective in reducing mechanical damage to fruit after 13 hours of transportation, with mechanical damage reaching 0 (zero) due to net foam. The type of packaging used had a significant effect on quality change of salak during storage, namely physical, physiological and microbiological damage, weight loss, hardness, and TSS. Cardboard packaging with net foam was the best treatment, showing low physiological and microbiological damage until the 16th day of storage, which amounted to 4.05, as well as a low rate of change in quality for 22 days. Keywords: Salak bunches, storage, packaging, fruit quality, transportation